Telepresence robots as facilitators of physical exercise during COVID-19: a feasibility and acceptance study - Addas, Abdullah (Frontiers in Public Health, 2023)
The COVID-19 pandemic and associated restrictions on mobility and access to green space have disrupted exercise habits worldwide. According to the World Health Organization (WHO), approximately 1.4 billion adults were insufficiently physically active in 2016, with detrimental impacts on health. The proposed study investigated the use of telepresence-robot-based personal trainers to facilitate remote exercise during the pandemic-related lockdowns. Several adults aged 18-65 were recruited for a four-week intervention and thorough research investigation. The intervention involved one-hour outdoor exercise sessions held three times per week in a local park with a human instructor connected via a telepresence robot. Surveys assessed perceptions of social presence, usability, the intention to use the robot and the psychological benefits of access to green space. System logs tracked participation and technical errors. At baseline, 30% of the participants met the WHO physical activity (PA) recommendations, compared to 80% after the intervention. The study shows significant increases in many parameters. These are perceived in social presence (p<0.021), usability (p<0.04), intentions for long-term use (p<0.05), and the mental health benefits of accessing green spaces (p<0.013). Attendance was found to be 90%, with a 7% technical failure rate. This investigation demonstrates the promise of telepresence robots for safely providing remote access to green spaces. They can be used to facilitate exercise during public health crises, overcoming the barriers to maintaining PA.